Methane Production from Pineapple Waste - Shahrulkalam, Muhammad Akmal; Seswoya, Roslinda (Journal of Advancement in Environmental Solution and Resource Recovery, 2026)
Pineapple is a fruit that is produced in large quantities, and anaerobic digestion can convert pineapple waste into methane, a renewable energy source that is environmentally friendly. Pineapple waste is usually burned or dumped in a landfill for disposal, which causes environmental pollution, including greenhouse gas emissions. The objectives of this study are to examine the methane production from pineapple waste. In this study, the methane production at a batch scale using pineapple waste (a combination of peel and pulp) inoculated with anaerobic microbes from the biogas plant inoculum was conducted. The batch reactor was operated at an inoculum-to-substrate ratio of 0.4, and water displacement was used to measure methane production. The characterization of pineapple waste and inoculum for both total solids and volatile solids follows the APHA 2005, while chemical oxygen demand was tested by using a HACH spectrophotometer. Methane generation was observed on day one (294 ml), and production gradually decreased starting from day 2. An acidic condition is the primary reason for the decline in methane production. In conclusion, pineapple waste has shown potential to generate methane. However, the appropriate experimental setup shall be provided to produce the consistent methane production.